2007
DOI: 10.1007/s10661-007-9898-5
|View full text |Cite
|
Sign up to set email alerts
|

Humidity and illumination organic semiconductor copper phthalocyanine sensor for environmental monitoring

Abstract: In this investigation properties of organic semiconductor copper phthalocyanine (CuPc) capacitive humidity and illumination sensors were studied. Organic thin film was deposited by vacuum evaporation on a glass substrate with silver surface-type electrodes to form the Ag/CuPc/Ag sensor. The capacitance of the samples was evaluated at room temperature in the relative humidity range of 35-92%. It was observed that capacitance of the Ag/CuPc/Ag sensor increases with increase in humidity. The ratio of the relative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(27 citation statements)
references
References 12 publications
0
26
0
Order By: Relevance
“…Relative humidity (RH) sensor is mainly used for monitoring atmospheric humidity environment and shows important applications in warehousing [1], environmental monitoring [2], instruments and meters, and meteorology [3]. Until now, various types of humidity sensors have been reported, such as resistance type [4], capacitor type [5], field-effect-transistor type [6], optical type [7, 8], and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Relative humidity (RH) sensor is mainly used for monitoring atmospheric humidity environment and shows important applications in warehousing [1], environmental monitoring [2], instruments and meters, and meteorology [3]. Until now, various types of humidity sensors have been reported, such as resistance type [4], capacitor type [5], field-effect-transistor type [6], optical type [7, 8], and so on.…”
Section: Introductionmentioning
confidence: 99%
“…These two situations can be illustrated as a charging capacitor in which the area under the curve corresponds to the stored charge. Indeed, Karimov et al observed capacitive changes on non-substituted CuPc-covered electrodes and exploited such effect in sensing devices [52]. From Fig.…”
Section: Resultsmentioning
confidence: 96%
“…Otherwise MPcs are insulating in high vacuum and dark environments [46,51]. Regarding humidity effects, Bohrer et al observed electrical current changes on cobalt and metal-free phthalocyaninebased chemiresistors due to the device exposure to water vapor, whereas Karimov and co-workers registered capacitance changes on copper phthalocyanine-coated electrodes for different RH values [51,52]. According to Bohrer et al vapor molecules in general interact at phthalocyanine free sites but can also compete for O 2 -bound sites [51,[53][54][55] and Karimov et al expect that water molecules can act as p-type dopants in MPcs similar to the O 2 effect [52].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we have used NiPc in illumination sensors, extending our previous work using CuPc [9]. One of the major advantages of NiPc over CuPc is that its charge carriers possess higher mobility (0.1 and 10 −4 cm 2 /V s for electrons and holes, respectively) [10].…”
Section: Introductionmentioning
confidence: 82%